Tweet Berbayar: Bagaimana Word-Of-Mouth Bekerja dalam Media Baru - Syaukat, Rosidah; Imanjaya, Ekky (Bina Nusantara University, 2011)
New media, like Twitter, has changed many possibilities, including marketing strategy in Indonesia. One of the extraordinary phenomena is paid-to-tweet, as being used by celebrity or ordinary users. The purpose of the article is to identify how Twitter roles in marketing: what the unique characteristic of Twitter so that Word-of-Mouth (WOM) could work effectively and efficiently? How viral marketing, buzz marketing and recommendation could move simultaneously to increase awareness to consumers about specific goods and services? How to choose the endorsers, as buzzers and key opinion leader in social media like Twitter? And why is hard-sale highly forbidden in new marketing practical style? Generally, the article will analyze about what and how regarding phenomena of paid-to-tweet happening in Indonesia.